Kaempferol, a Major Flavonoid in Ginkgo Folium, Potentiates Angiogenic Functions in Cultured Endothelial Cells by Binding to Vascular Endothelial Growth Factor - Hu, Wei-Hui; Wang, Huai-You; Xia, Yi-Teng; Dai, Diana Kun; Xiong, Qing-Ping; Dong, Tina Ting-Xia; Duan, Ran; Chan, Gallant Kar-Lun; Qin, Qi-Wei; Tsim, Karl Wah-Keung (Frontiers in Pharmacology, 2020)
Kaempferol is a major flavonoid in Ginkgo Folium and other edible plants, which is being proposed here to have roles in angiogenesis. Angiogenesis is important in both physiological and pathological development. Here, kaempferol was shown to bind with VEGF, probably in the heparin binding domain of VEGF: this binding potentiated the angiogenic functions of VEGF in various culture models. Kaempferol potentiated the VEGF-induced cell motility in human umbilical vein endothelial cells (HUVECs), as well as the sub-intestinal vessel sprouting in zebrafish embryos and formation of microvascular in rat aortic ring. In cultured HUVECs, application of kaempferol strongly potentiated the VEGF-induced phosphorylations of VEGFR2, eNOS and Erk in time-dependent and concentration-dependent manners, and in parallel the VEGF-mediated expressions of matrix metalloproteinases (MMPs), MMP-2 and MMP-9, were significantly enhanced. In addition, the potentiation effect of kaempferol was revealed in VEGF-induced migration of skin cell and monocyte. Taken together, our results suggested the pharmacological roles of kaempferol in potentiating VEGF-mediated functions should be considered.